Geospatial Fluid Milk Processing Preferences: Is Consumer Taste Perception the Key Factor? - Kasey M. Schalich; Paul A. LaPierre; Vimal Selvaraj (Dairy, 2022)
Consumption of ultrapasteurized milk is marked by extensive global variability; in the U.S. and U.K., less than 10% of fluid milk is marketed as ultrapasteurized, compared to >80% in France, Spain and Portugal. Fluid milk taste perception amongst U.S. consumers is that high-heat treatment of milk, as in ultrapasteurization, generates undesirable differences in taste compared to low-temperature/conventional pasteurized treatment. Although highly trained experts can distinguish characteristics in controlled studies, it remains unknown if general consumers can detect a difference or are subject to confirmation bias. In testing sensory perception in a defined untrained population, our findings indicate that the general consumer is unable to distinguish ultrapasteurized from pasteurized milk. On this basis, we conclude that presumptive “consumer taste perception” that speciously impacts fluid milk processing types in the U.S. market precludes noted benefits to ultrapasteurization not only in flexibility for storage and distribution, but also in reduction of public health risks.